2010
DOI: 10.1093/ejo/cjq019
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of orthodontic bonding adhesive resins on human oral fibroblasts

Abstract: There is little information concerning the cytotoxic effects of no-mix and flowable adhesives used in orthodontics. The aim of the present study was to evaluate the cytotoxic effects of a no-mix (Unite), a light-cured (Tranbond XT), and a flowable (Denfil Flow) adhesives on human oral fibroblasts. Twelve discs of each adhesive were prepared and aged for 1, 3, 5, and 7 days in Dulbecco's Modified Eagle's Medium (DMEM). Cell viability was assessed by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 42 publications
2
44
1
2
Order By: Relevance
“…1 On the other hand, the monomers released by resins are cytotoxic to fibroblasts, 13 which can induce local and systemic reactions in patients, 14 causing epithelial proliferation, lichenoid reactions, 15 hypersensitivity, and allergic reactions. 15,16 The main cause of the cytotoxic effects of resins is the release of unpolymerized residual monomers, 2,7,11,17 which may cause severe cellular damage 3,10,17 and favor bacterial growth around the resin. 18 Studies 19,20 have demonstrated that flowable resins are more cytotoxic than traditional resin composites.…”
Section: Discussionmentioning
confidence: 99%
“…1 On the other hand, the monomers released by resins are cytotoxic to fibroblasts, 13 which can induce local and systemic reactions in patients, 14 causing epithelial proliferation, lichenoid reactions, 15 hypersensitivity, and allergic reactions. 15,16 The main cause of the cytotoxic effects of resins is the release of unpolymerized residual monomers, 2,7,11,17 which may cause severe cellular damage 3,10,17 and favor bacterial growth around the resin. 18 Studies 19,20 have demonstrated that flowable resins are more cytotoxic than traditional resin composites.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesive specimens were prepared in the same thickness as that used under brackets to provide data relevant to the clinical conditions. 17,25 HGF cells were selected because of their abundance in the gingiva where excess bonding material would be frequently observed. The MTT assay used in this study is a simple, sensitive, reliable and commonly used enzymatic assay to determine the cytotoxicity of various medicinal and toxic materials.…”
Section: Discussionmentioning
confidence: 99%
“…Biocompatibility of different types of orthodontic adhesives and their ingredients have been investigated in several studies and most indicated cytotoxic effects of different intensity, 17-20 due to the release of unbound molecules from the structure of cured composites. 17,21 Incorporation of nano-particles to composite structure may result in additional health hazards because of the specific structural and chemical properties of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diğer taraftan, adeziv kalınlığın-daki artış yetersiz aktivatör penetrasyonuna sebep olacağından homojen olmayan polimerizasyon paterni üreterek, sitotoksisiteyle sonuçlanacaktır. 32 Polimerizasyon derecesi, bir rezin adezivin ne kadar polimerize olduğunu ifade eder ve monomer moleküllerin ve materyale ulaşan ışık ve enerjinin özelliklerine bağlıdır. Polimerizasyon derecesi arttıkça, rezin adevizin çözünürlüğü ve bozulması azalmaktadır.…”
Section: Rezin Adezivler Ve Bonding Ajanlarunclassified